2011
DOI: 10.1556/abiol.62.2011.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a porphyrazine derivative on some developmental characteristics ofDrosophila melanogaster

Abstract: In this study, the effects of a porphyrazine derivative, [octakis (2-trimethylammoniumethyl thio) porphyrazinatocobalt] octaiodide (CoPzq), were explored on the developmental characteristics, sex ratio and egg fertility of Drosophila melanogaster. CoPzq was preferred in the study due to its probability to be used as a chemotherapeutic agent in medicine. As a result of the application of CoPzq, a phenotypic abnormality was revealed within the individuals of F1 and F2 generation of Drosophila. Although individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The results of the present study showed that kefir, yogurt, and milk reduced the number of adults in Drosophila , thereby impeding development. The observation of a decrease in the number of adults in Drosophila is usually a result of the application of toxic substances ( Karataş and Bahçeci 2009a , Karataş et al 2011a , Karataş et al 2011b , Keser and Karataş 2012 ). Hence, it was unexpected that foods that are nutritious and beneficial for humans had such negative effects on Drosophila that they could be considered toxic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the present study showed that kefir, yogurt, and milk reduced the number of adults in Drosophila , thereby impeding development. The observation of a decrease in the number of adults in Drosophila is usually a result of the application of toxic substances ( Karataş and Bahçeci 2009a , Karataş et al 2011a , Karataş et al 2011b , Keser and Karataş 2012 ). Hence, it was unexpected that foods that are nutritious and beneficial for humans had such negative effects on Drosophila that they could be considered toxic.…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that the substances added to the medium do not increase the rate of these mutations. However, in toxic drug applications to Drosophila , these mutations increase and the rate of abnormal phenotypes also increases ( Karataş and Bahçeci 2009b , Karataş and Bahçeci 2010 , Karataş et al 2011a , Karataş et al 2012 ). Hence, it appears that kefir, yogurt, and milk negatively affect development but do not increase the rate of mutation causing the increase in abnormal phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations